Forced Overexpression of Signal Transducer and Activator of Transcription 3 (STAT3) Activates Yes-Associated Protein (YAP) Expression and Increases the Invasion and Proliferation Abilities of Small Cell Lung Cancer (SCLC) Cells - Ping-Chih Hsu; Jhy-Ming Li; Cheng-Ta Yang (Biomedicines, 2022)
Background: We sought to investigate the interaction between signal transducer and activator of transcription 3 (STAT3) and the Yes-associated protein (YAP) signaling pathway in human small cell lung cancer (SCLC) cells. Methods: The STAT3-overexpressing SCLC cell lines H146 and H446 were established by plasmid DNA transfection for in vitro and in vivo experiments. Results: Overexpression of STAT3 increased YAP protein expression in H146 and H446 cells. STAT3 overexpression significantly increased YAP mRNA expression and the mRNA expression of the YAP signaling downstream genes CTGF and CYR61 in H146 and H446 cells (p < 0.05). We showed that STAT3 overexpression promoted EMT (epithelial–mesenchymal transition) with increased matrix metalloproteinase (MMP)-2 and MMP9 expression. Transwell assays showed that STAT3 overexpression increased the invasion ability of H146 and H446 cells. In addition, STAT3-overexpressing H146 cells grew significantly more rapidly than control H146 cells in the xenograft mouse model (p < 0.05). Immunohistochemistry (IHC) staining and Western blotting (WB) showed that STAT3-overexpressing H146 tumors had increased p-STAT3 and YAP staining and protein expression compared with control tumors. Increased EMT was also observed in STAT3-overexpressed xenograft tumors. Conclusions: The results of our study suggest that the overexpression of STAT3 promotes SCLC EMT, invasion, and proliferation through the activation of the YAP signaling pathway.